Progress in the Research of the Toxicity Effect Mechanisms of Heavy Metals on Freshwater Organisms and Their Water Quality Criteria in China - Ya-jun Hong; Wei Liao; Zhen-fei Yan; Ying-chen Bai; Cheng-lian Feng; Zu-xin Xu; Da-yong Xu (Journal of Chemistry)
Water quality criteria are the scientific basis for formulating water quality standards and environmental management practices. Due to the development of urbanization and industrialization, the problem of heavy metal pollution has become a serious environmental problem. Heavy metals not only have major impacts on aquatic organisms, but also seriously threaten human health. However, the current environmental criteria refer to the maximum value limitations of environmental factors in environmental media where harmful or detrimental effects are not produced on specific protected objects. This study reviewed the sources, hazard levels, toxic effect mechanisms, and the current research status of China’s water quality criteria for heavy metal pollutants. In addition, the focus and direction of future research on the toxic effects of heavy metal on aquatic organisms and the necessary criteria changes were discussed. The present study would provide an important theoretical basis for the future research of water quality criteria and risk assessment of heavy metal pollutants.